Nonallergic hypersensitivity to nonsteroidal antiinflammatory drugs, angiotensin-converting enzyme inhibitors, radocontrast media, local anesthetics, volume substitutes and madications used in general anesthesia - Jurakić-Tončić, Ružica (Array, 2009)
Summary: Urticaria and angioedema are common allergic manifestations and medications are one of common triggering factors. The most severe immediate drug reaction is anaphylaxis. Apart from the well established IgE-mediated immediate type hypersensitivity reactions, the pathogenesis of drug-induced urticaria, angioedema and anaphylaxis often remains obscure. In this article, emphasis is put on nonallergic reactions to the most commonly used drug groups of nonsteroidal antiinflammatory drugs, angiotensin- converting enzyme inhibitors, radiocontrast media, volume expanders and drugs used in general anesthesia. Urticaria is the second most common drug eruption after maculopapular exanthema. The mechanisms of acute urticarial reactions are multiple, mostly IgE mediated, but some drugs can induce immune complex reactions and activate complement cascade, while others can induce direct activation of mast cells and degranulation or activation of complement by non-immune mechanisms. With different types of medications different pathomechanisms are involved. Non-steroid anti-inflammatory drugs are thought to cause reaction due to cyclooxygenase-1 inhibition and overproduction of leukotrienes, blamed for cutaneous and respiratory symptoms. Angiotensin-converting enzyme inhibitors can cause fatal angioedema, which is partially explained with bradykinin excess and impairment of aminopeptidase P and dipeptidyl peptidase IV that are involved in the metabolism of substance P and bradykinin. It remains unknown what additional mechanisms are involved. Radiocontrast media and local anesthetics mostly cause nonallergic hypersensitivity reaction, but in rare cases true allergic reaction can occur. Dextran is known to cause IgG mediated, immune complex anaphylaxis and it is recommended to use human serum albumin as the safest colloid